Sehat Tanpa Asap Rokok Dusun III Desa E Wonokerto Kabupaten Musi Rawas - Marmini; Jannah , Erna Miftakhul; Fajariyani , Sella; Tranado, Hengki (Jurnal Pakar Pengabdian Kesehatan, 2025)
Smoking is one of the main risk factors for several chronic diseases that can cause death. Many studies have shown that smoking behavior can increase the risk of various diseases that can cause death. This shows that smoking is a major problem for public health (Prihatiningsih et al., 2020). A report from the World Health Organization (WHO) in 2019 stated that over the past two decades, overall tobacco users (cigarettes, cigars, kretek cigarettes) globally have decreased. In 2010, the number of tobacco users or smokers recorded was 1.397 billion people worldwide, while in 2018 the figure decreased to 1.337 billion. The decline in this figure proves that in the past two decades, the number of tobacco users or smokers has decreased by around 60 million people worldwide. Despite the decline, the prevalence of smokers is still very high and can have a bad impact (Kaniawati et al., 2021). Based on data from Based on the report of the Central Statistics Agency (BPS), the percentage of the Indonesian population aged 15 years and over who smoked in the past month was 28.62% in 2023. This percentage increased by 0.36% points from last year which was 28.26%. For the South Sumatra region, it is still high with a value of 30.91% and for data on residents of hamlet III in E. Wonokerto village who actively smoke, there are still 30 residents who smoke, dominated by fathers. The method used in this counseling is to distribute leaflets and questions and answers. The purpose of this activity is to change a healthy lifestyle without cigarette smoke to implement a healthy home environment without cigarette smoke.